Winning the story wars : why those who tell--and live--the best stories will rule the future - Sachs, Jonah (Harvard Business Review Press, 2012)
"The story wars are all around us. They are the struggle to be heard in a world of media noise and clamor. Today, most brand messages and mass appeals for causes are drowned out before they even reach us. But a few consistently break through the din, using the only tool that has ever moved minds and changed behavior -- great stories. With insights from mythology, advertising history, evolutionary biology, and psychology, viral storyteller and advertising expert Jonah Sachs takes readers into a fascinating world of seemingly insurmountable challenges and enormous opportunity. You'll discover how: Social media tools are driving a return to the oral tradition, in which stories that matter rise above the fray ; Marketers have become today's mythmakers, providing society with explanation, meaning, and ritual ; Memorable stories based on timeless themes build legions of eager evangelists ; Marketers and audiences can work together to create deeper meaning and stronger partnerships in building a better world ; Brands like Old Spice, The Story of Stuff, Nike, the Tea Party, and Occupy Wall Street created and sustained massive viral buzz."--Publisher.